A new bamboo-feeding species of Kaochiaoja Tao (Hemiptera: Aphididae) from India - Joshi, Sunil; Blackman, R. L. (Zootaxa, 2017)
A new species of the genus Kaochiaoja Tao 1963, K. sikkimensis sp. n., was collected on Phyllostachys sp. (Poaceae) from Upper Tadong area of Gangtok, East Sikkim, India. Apterous and alate viviparae of this species are described, illustrated and discussed in comparison with the only other nominal species in this genus.